ULTRASONOGRAPHIC MEASUREMENT OF PROSTATIC SIZE IN ,INTACT NON-DESCRIPT DOGS - KADAMBARl, V; CHANDRASEKARAN, D; JEYARAJA, K; THIRUNAVUKKARASU, P S (The Indian Journal of Animal Reproduction, 2023)
The present study was carried out to estimate the prostatic size in 38 intact, non-descript dogs using ultrasonography. The mean prostate length (L), prostate depth on longitudinal section(DL), prostate depth on transverse section (DT) and prostate width (W) was 3.2 ± 0.60 cm, 2.65 ± 0.60 cm, 2.67± 0.54 cm and 3.02 ± 0.54 cm respectively. The mean prostatic volume (PV) and prostatic weight (PW) was 20.19 ± 3.92 cm3 and 17.61 ± 7.42 g respectively. The study showed that there was statistically significant correlation between body weight or age and prostatic dimensions (L, DL, DT and W).